Acute neuroinflammation, sickness behavior and working memory responses to acute systemic LPS challenge following noradrenergic lesion in mice - Cunningham, Colm; Harkin, Andrew (My University, 2021)
Locus coeruleus (LC)-derived noradrenaline is important in cognition and decreases with age, but the impact of prior noradrenaline deficiency on vulnerability to inflammation-induced acute cognitive dysfunction is unclear. Here we assessed whether noradrenergic depletion, in female mice, impacted upon inflammation, locomotor activity and working memory directly after acute systemic immune challenge with bacterial lipopolysaccharide (LPS), a paradigm we have previously used to capture delirium-like acute cognitive deficits. Mice received 2 doses of the LC-selective noradrenergic toxin N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine (DSP-4; 50 mg/kg i.p.) and were challenged, 2 weeks later, with LPS (100 μg/kg i.p.). DSP-4 dramatically reduced noradrenaline concentrations and tyrosine hydroxylase-positive afferents in the frontal cortex and hippocampus. This did not significantly alter numbers of Pu.1-positive microglia, Iba1-positive microglial morphology or mRNA expression of microglia-associated gene transcripts (Tyrobp, Sall1, Cd68, Sra2, Clec7a) in the hippocampus or frontal cortex and produced modest reductions in Cx3cr1 and P2ry12. LPS induced blood and brain cytokine levels, cFOS activation and locomotor responses that were highly similar in DSP-4- and vehicle-treated mice, although LPS- induced plasma TNF-α was significantly reduced in those treated with DSP-4. Importantly, prior noradrenergic depletion did not predispose to LPS-induced T-maze working memory deficits. The data demonstrate that significant depletion of noradrenaline in the hippocampus and frontal cortex does not prompt acutely exaggerated neuroinflammation or leave the brain vulnerable to acute, transient working memory deficits upon low dose LPS challenge. These findings have implications for our understanding of the impact of systemic inflammation on the aging and vulnerable brain during septic encephalopathy and delirium.
PUBLISHED
cited By 4
Keywords: Locus coeruleus (LC)-derived noradrenaline; acute cognitive dysfunction; systemic inflammation; Working memory; Noradrenaline; Microglia; Inflammation; Delirium; Neuroscience